New directions for academic liaison librarians - Crawford, Alice, 1958-; ScienceDirect eBooks (Oxford : Chandos Publishing, 2012)
Shows how liaison librarians can extend their roles beyond the established one of information literacy teaching and showcases areas in which they can engage in collaborative ventures with academic and administrative staff. --from publisher description.
Introduction -- Liaison in the wider world: a medical library in Malawi -- Liaison and bibliometric support: the UK Research Assessment Exercise -- LIaison and virtual worlds -- Liaison and digital scholarship -- Liaison and open access journals -- Liaison and community outreach: a Friends of the Library Group -- LIaison and library buildings -- Conclusion -- References and further reading -- Index.
Includes bibliographical references and index.
Safari Books Online
Elsevier
Keywords: Academic libraries; Academic librarians -- Professional relationships; LANGUAGE ARTS & DISCIPLINES -- Library & Information Science -- General; Academic libraries; Electronic books